Hydrographical time series data of Helgoland, Southern North Sea, 2024 - Philipp Fischer; Miriam Lienkämper; Markus Brand; Ingeborg Bussmann; Holger Brix (PANGAEA, 2025)
The dataset contains temperature, salinity, oxygen saturation, chlorophyll a and turbidity data from the Helgoland MarGate underwater observatory from the year 2024 in a temporal resolution of 1 hour. The cabled observatory is located in 10m water depth and comprises single or multiple sensors for a specific parameter (see https://www.awi.de/en/science/biosciences/shelf-sea-system-ecology/main-research-focus/cosyna/underwater-node-helgoland.html). For a detailed description of the data see associated metadatafile metadata_heluwobs_2024_hydrography.pdf.